THE INFLUENCE CUSTOMER TRUST, SERVICE QUALITY, AND PERCEIVED PRICE ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY - MANDIRA, DARA AJENG; SULIYANTO, SULIYANTO; NAWARINI, ALISA TRI (INDONESIAN RESEARCH SOCIETY, 2018)
The purpose of this research is to know and analyze the influence customer trust, servicequality, and perceive price of expedition company towards customer satisfaction, effectedtoo on customer loyalty. The sample in this study there are 100 respondents.Conveniencesampling method is used in the determination of this research sample. Data were analyzedusing Structural Equational Modeling (SEM) with SPSS and AMOS statistical software.Theresults of this study show that cusotmer trust, customer satisfaction, service quality,perceived price has a positive effect on Customer Satisfaction. Thus, customer satisfactionhas a positive effect on customer loyalty.